The Effect of the Legislative Development on the Organization and Jurisdiction of the Jordanian Administrative Judiciary - Al-Qadi , Waleed (Dirasat: Shari’a and Law Sciences, 2020)
The oversight of the administrative judiciary represents a real guarantee for the work of the administration and for public rights and freedoms, and an effective protection of the principle of legality. The problem of the research is that the oversight of the Jordanian administrative judiciary is limited to examining the legality of the contested administrative decision, stopping it and compensating for it in the event of its illegality being judged only. In order to clarify the importance, problem, and limits of the impact of legislative development on the organization and jurisdiction of the Jordanian administrative judiciary, the comparative descriptive analytical method was followed in examining the issues of the administrative judiciary. These topics are the organization of the administrative judiciary and the statement of its judicial competencies. Perhaps one of the most prominent results we have reached is that the judicial system in Jordan is based on partial bilateral oversight, making judicial oversight over the work of the administration at times the jurisdiction of the administrative judiciary, and at other times the jurisdiction of the ordinary judiciary. As for the most important recommendations, it is the need for the legislator to intervene by stipulating the establishment of an independent state council consisting of two sections: a judicial section specialized in handling all administrative disputes and an administrative section specialized in drafting legislation and providing fatwas, and legal opinions, similar to countries with a dual judicial system.